Visual Loss Due to Retinal Disorders: A study on 1496 Cases (Medical Forum Monthly, 2021)
Objective: The aim of this hospital based study is to ascertain the frequency of various retinopathies in the upper Sindh.Study Design: quasi experimental studyPlace and Duration of Study: This study was conducted at the CMC and KMC for duration of January, 2016 to January, 2021 for a period of 5 years.Materials and Methods: Patients with retinal disorders were selected as they came to the OPD for checkup or were referred to from other centers. A complete history and ocular examination along with biochemical test and radiological investigations were thoroughly carried out at the institution with strict protocols being followed at every step. Data was collected accordingly and analyzed using SPSS. All the data was quantitative and hence represented as frequency and percentage.Results: A total of 1496 patients were included in the study that were diagnosed with retinal disorders, 963 (64.37%) Male and 533 (35.62%) Female aged between 3-92 years. 625 (41.77%) Patients had diabetic retinopathy in which 234 had Non-Proliferative Diabetic Retinopathy, 216 had Proliferative Diabetic Retinopathy, and 387 had clinically significant macular Edema. Retinal Vein occlusion was found in 116 (7.75%) of the patients in which 73 had Central Retinal Vein Occlusion, 34 Branch Retinal Vein Occlusion, and 9 had Hemiretinal Vein Occlusion. Central Serous Chorioretinopathy was seen in 102 (6.81%) of patients aged 17-55 years. Retinal Vasculitis was seen in 70 (4.67%) patients aged 16-60 years.Conclusion: Diabetic Retinopathy was amongst the most prevalent retinal vein disorder. Others in high frequency included retinal vein occlusion, Central Serous Chorioretinopathy, and Retinal Vasculitis.